Popularity and impact of using smart devices in medicine: experiences in Saudi Arabia - Sameer Al-Ghamdi (BMC, 2018)
Abstract Background The present study aimed to investigate smart device medical apps currently preferred by physicians in Saudi Arabia and the perceived impact of the apps on patient care. Methods Questionnaires for this cross-sectional study on smart device medical apps were randomly emailed to 384 physicians registered in the Saudi Commission of Health Specialists database. A total of 300 physicians returned completed questionnaires, with a response rate of 78.5%. Physician demographics and their perceptions of medical apps were assessed, including questions on the purpose, impact, and types of medical apps used. Questions were answered using a Likert scale (1 = strongly disagree, 2 = disagree, 3 = not sure, 4 = agree, and 5 = strongly agree). Results Study subjects had a median age of 39 years (57.7% male). Most respondents (88.3%) had smart devices, and 86.3% had at least one medical app installed. Just over half used an app at least once a day (53.0%). Medical apps were positively perceived, with physicians reporting increased dependency on the apps (Likert score: 4.7 ± 0.5). Conclusion Medical apps were perceived to positively impact education, physician efficiency, and patient care.